The impact of intensive urbanization in Tashkent on economic stability, environmental conditions, and demographic processes - Khandamirdzhanova B.M.; Shoislomova , Komila (GREEN ECONOMY AND DEVELOPMENT, 2025)
Urbanization is the backbone of economic development, but it can also lead to serious disaster in terms of its speedy and ungoverned character. The case study, focus on Tashkent, by describing the economic instability, environmental degradation, and demographic pressures caused by intensive urbanization, shows an example of “urbanaffected economic and social issues”. It causes distortions in the housing market, increases the cost of living, destroys the environment and encourages unsustainable population growth in the capital. This study, using empirical data and case studies, illustrates the consequences of unrestrained urban growth. The insights are important for urban policy discourse as it helps acknowledge significant stressors, providing guidance for urban planning that is equitable and balanced, and even emphasizing safeguards for sustainable development, that are effective in managing resources and regulatory measures to avert prolonged crises over time.